1973
DOI: 10.2307/1379128
|View full text |Cite
|
Sign up to set email alerts
|

Body Composition, Energy Content, and Lipid Cycles of Four Species of Rodents

Abstract: GroSS body composition, energy content, and lipid cycles of Peromyscus maniculatus, Reithrodontomys megalotis, Sigmodon hispidus, and Microtus ochrogaster were studied. Ash values for adults ranged from 14.2 to 16.1 per cent of dry body weight, and water content varied from 61.5 to 74.2 per cent. Lipid content ranged from a low of 14.6 per cent dry body weight in M. ochrogaster to a high of 25.6 per cent in S. hispidus. Annually, kilocalories per gram live weight averaged 1.61 in P. maniculatus, 1.65 in R. meg… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
19
2
4

Year Published

1975
1975
2022
2022

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 66 publications
(29 citation statements)
references
References 16 publications
4
19
2
4
Order By: Relevance
“…Values were similar to those reported for other species {e.g., Bailey et al 1960;G贸recki, 1965;Fleharty et al 1973) and support the suggestion that this component varies within narrow limits in small mammals. It is reasonable, therefore, to assume ash content has no appreciable effect on seasonal variation in live weight caloric content.…”
Section: Discussion Of Resultssupporting
confidence: 89%
“…Values were similar to those reported for other species {e.g., Bailey et al 1960;G贸recki, 1965;Fleharty et al 1973) and support the suggestion that this component varies within narrow limits in small mammals. It is reasonable, therefore, to assume ash content has no appreciable effect on seasonal variation in live weight caloric content.…”
Section: Discussion Of Resultssupporting
confidence: 89%
“…The interspecific comparison of the means shows that S. cinereus is 4% lower than the other species, which is about twice the value found by G贸recki (1965). Fleharty et al (1973) found high values of ash contents (14.2-16.2%) and suggested that this might have been due to the age structure of the population. I mentioned in an earlier section that my smalLmammal sample was not at an uniform adult stage, and contained thus several juvenile and subadult animals.…”
Section: Caloric Value Of Ash-free Weightmentioning
confidence: 60%
“…Seasonal differences in water content have been demonstrated in ten species inhabiting different geographical regions and differentiated in respect of their ways of living (G贸recki, 1965;Fleharty, et al, 1973; Sa wicka-Kapusta, 1974; Schreiber & Johnson, 1975). In these rodents the water content was compared with the body weight and sometimes with the contents removed from the stomachs.…”
Section: Discussionmentioning
confidence: 99%